2021
DOI: 10.12659/msm.930639
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Recent Research on the Role of MicroRNAs in Renal Cancer

Abstract: Renal cell carcinoma (RCC) is a most common type of urologic neoplasms; it accounts for 3% of malignant tumors, with high rates of relapse and mortality. The most common types of renal cancer are clear cell carcinoma (ccRCC), papillary renal cell carcinoma (pRCC), and chromophobe renal carcinoma (chRCC), which account for 90%, 6–15%, and 2–5%, respectively, of all renal malignancies. Although surgical resection, chemotherapy, and radiotherapy are the most common treatment method for those diseases, their effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 125 publications
(129 reference statements)
0
11
0
Order By: Relevance
“…The analysis showed that some extreme emotions such as fear and anxiety were avoided through popularization of disease-related knowledge, correction of patients' wrong cognition, and establishment of correct concept of treatment during nursing [ 17 ]. In addition, psychological counseling is conducted for the patients to achieve the optimal psychological state as much as possible so as to regulate the hypothalamic and adrenal sympathetic nervous system of the patients and reduce the massive secretion of cortisol and adrenocortical hormone in the body caused by negative emotions, thereby avoiding stress response to a great extent [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis showed that some extreme emotions such as fear and anxiety were avoided through popularization of disease-related knowledge, correction of patients' wrong cognition, and establishment of correct concept of treatment during nursing [ 17 ]. In addition, psychological counseling is conducted for the patients to achieve the optimal psychological state as much as possible so as to regulate the hypothalamic and adrenal sympathetic nervous system of the patients and reduce the massive secretion of cortisol and adrenocortical hormone in the body caused by negative emotions, thereby avoiding stress response to a great extent [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that miRNAs can regulate the proliferation of Rcc cells (14)(15)(16). Therefore, the present study first analyzed the global changes in the miRNA expression profile following TGF-β1 treatment.…”
Section: Global Effects Of Tgf-β1 On Mirnas Expression In Rccmentioning
confidence: 99%
“…[49][50][51] According to the reports published to date, the molecular mechanisms involved in the development of renal cancer are very complex and may even contain multiple signalling pathways. [52][53][54] Elucidating the mechanisms involved will involve the joint research efforts of multiple laboratories around the world.…”
Section: Discussionmentioning
confidence: 99%